Gerakan Peduli Pendidikan Masyarakat Berbasis Komunitas: Studi Kasus Komunitas Ruang Desa - Anwar, Chairuddin; Dwijayanto, Arik; Wathoni, Syamsul (Kodifikasia, 2025)
The background of this research highlights the educational gap between urban and rural areas in Indonesia, particularly in terms of access, quality, and infrastructure. In response, community-based movement initiatives such as Ruang Desa Literacy Community in Sampung Village, Ponorogo, driven by local youth. The research objectives were to analyze (1) the role of youth in developing community education, (2) the impact of the community on village literacy and education, and (3) the movement's sustainability model. The methodology used a qualitative case study approach with Robert Putnam's social capital theory (networks, norms, and trust). The results showed that the youth successfully built social capital through Bonding capital (internal youth cohesion), Bridging capital (networks with village government and communities), and Linking capital (partnerships with external institutions, such as the National Library). The impacts included increased youth participation in village governance, the establishment of Community Reading Gardens (TBM), and increased community literacy. The sustainability model rests on four pillars: self-funding (membership fees, donations), capacity building and regeneration, strategic partnerships, and knowledge management through TBM. Recommendations include the need for policy support to replicate similar models in other rural areas and to increase community legitimacy through formal recognition.